KEMAMPUAN MAHASISWA DALAM MENGANALISIS MATERI IPA SMP BERDASARKAN TAKSONOMI KOGNITIF, PSIKOMOTOR DAN AFEKTIF - Ratna Yulinda (FKIP ULM, 2018)
Abstract. The purpose of this study was to improve the ability of students to analyze science learning material based on cognitive, psychomotor, and affective domains. This Classroom Action Research uses the Kemmis & Taggart design. The subjects of this study were students of Science Education Study Program of Lambung Mangkurat University. The research instrument used was an observation sheet in the form of a check list. The results showed an increase in the ability of students from the dominant was quite good (55.32%) in the first cycle to be dominant in the criteria of good (63.83%) in the second cycle. Keywords: science learning material analysis, cognitive, psychomotor, affective Abstrak. Tujuan penelitian ini adalah untuk meningkatkan kemampuan mahasiswa dalam menganalisis materi IPA berdasarkan ranah kognitif, psikomotor, afektif. Penelitian Tindakan Kelas ini menggunakan desain Kemmis & Taggart. Subyek penelitian ini adalah mahasiswa program studi pendidikan IPA Universitas Lambung Mangkurat. Instrumen penelitian menggunakan lembar pengamatan dalam bentuk check list. Hasil penelitian menunjukkan peningkatan kemampuan mahasiswa dari dominan cukup baik (55, 32%) pada siklus I menjadi dominan pada kriteria baik (63, 83%) pada siklus II. Kata kunci: analisis materi IPA, kognitif, psikomotor, afektif